The Role of Ownership Structure in Moderating The Relationship Between Tax Avoidance, Corporate Social Responsibility Disclosure, and Firm Value - Kenny Ardillah; Ririn Breliastiti; Temy Setiawan; Nera Marinda Machdar (Accounting Analysis Journal, 2022)
Purpose: The company’s existence can be maintained by increasing the firms value every period, which will affect the welfare of investors. This study aims to examine and analyze the effect of tax avoidance, corporate social responsibility disclosure on firm value with managerial ownership as a moderating variable. Method: This study uses a sample of mining companies listed on the Indonesia Stock Exchange for 2016-2019. In this study, tax avoidance uses the Effective Tax Rate proxy, and corporate social responsibility disclosure uses the Corporate Social Responsibility Index. Firm value is measured using Tobin’s Q, and ownership structure as a moderating variable is measured by managerial and institutional ownership proxies. Findings: The results showed that tax avoidance and corporate social responsibility disclosure had no effect on firm value with firm size and capital intensity as control variables. Managerial ownership and institutional ownership significantly impact the relationship between tax avoidance and firm value with firm size and capital intensity as control variables. Managerial ownership and institutional ownership have no significant effect in moderating the relationship between corporate social responsibility disclosure and firm value with firm size and capital intensity as control variables. Novelty: The research used institutional ownership and managerial ownership as part of ownership structures to moderate the relationship between tax avoidance, corporate social responsibility disclosure, and firm value. Keywords: Tax Avoidance; Corporate Social Responsibility Disclosure; Firm Value; Ownership Structure; Managerial Ownership; Institutional Ownership